Early IV‐injected human dermis‐derived mesenchymal stem cells after transient global cerebral ischemia do not pass through damaged blood–brain barrier. (3rd June 2018) - Ahn, Ji Hyeon; Chen, Bai Hui; Park, Joon Ha; Shin, Bich Na; Lee, Tae‐Kyeong; Cho, Jeong Hwi; Lee, Jae Chul; Park, Jeong‐Ran; Yang, Se‐Ran; Ryoo, Sungwoo; Shin, Myoung Cheol; Cho, Jun Hwi; et al.
Abstract: There is lack of researches on effects of intravenously injected mesenchymal stem cells (MSCs) against transient cerebral ischemia (TCI). We investigated the disruption of the neurovascular unit (NVU), which comprises the blood–brain barrier and examined entry of human dermis‐derived MSCs (hDMSCs) into the damaged hippocampal CA1 area in a gerbil model of TCI and their subsequent effects on neuroprotection and cognitive function. Impairments of neurons and blood–brain barrier were examined by immunohistochemistry, electron microscopy, and Evans blue and immunoglobulin G leakage. Neuronal death was observed in pyramidal neurons 5‐day postischemia. NVU were structurally damaged; in particular, astrocyte end‐feet were severely damaged from 2‐day post‐TCI and immunoglobulin G leaked out of the CA1 area 2 days after 5 min of TCI; however, Evans blue extravasation was not observed. On the basis of the results of NVU damages, ischemic gerbils received PKH2‐transfected hDMSCs 3 times at early times (3 hr, 2, and 5 days) after TCI, and fluorescence imaging was used to detect hDMSCs in the tissue. PKH2‐transfected hDMSCs were not found in the CA1 from immediate time to 8 days after injection, although they were detected in the liver. Furthermore, hDMSCs transplantation did not protect CA1 pyramidal neurons and did not improve cognitive impairment. Intravenously transplanted hDMSCs did not migrate to the damaged CA1 area induced by TCI. These findings suggest no neuroprotection and cognitive improvement by intravenous hDMSCs transplantation after 5 min of TCI.